POSITIVE SPORT ORGANIZATIONAL INSIGHTS - Kim, Minjung; Oja, Brent D.; Anagnostopoulos, Christos, 1978- (ROUTLEDGE, 2025)
"This book is a concise and accessible introduction to positive organizational behavior in sport, a new and dynamic approach to sport management. Clearly explaining core concepts, including the central concept of psychological capital, the book shows how 'positive sport organizations' (PSO) can deliver improved performance and enhance employee well-being. Standing at the intersection of positive psychology and theories of organizational behavior, the PSO approach focuses on the development of the person within the organization - their human strengths and psychological capacities - in contrast to traditional approaches that have a more limited emphasis on human capital or social capital. The book takes a close look at attributes including passion, grit, and a capacity for innovation, that characterize the effective employee in the modern, fast-paced sport business environment and that can be developed through PSO, and it explains how employee flourishing and corporate social responsibility programmes can be mutually reinforcing. With examples and cases from contemporary sport business in every chapter, this is illuminating reading for any student, researcher, policy-maker or practitioner with an interest in sport business and management, organizational behavior, corporate social responsibility, human resource management, or human flourishing"-- Provided by publisher.
Keywords: Sports administration.; Organizational behavior.; Sports administration -- Vocational guidance.; Personnel management.; elektronické knihy; electronic books